Event (de)composition - Chen, SY; Husband, EM (Oxford University Press, 2019)
Grammatical theories of event structure have broadly proposed that event representations are decomposed and articulated in a variety of different constituents across a sentence. These theories raise questions for sentence comprehension: how are cues to these disparate components recognized and put back together to construct a complete and coherent representation of the event under discussion? Such questions are made all the more complex during real-time processing as these components arrive one after another in quick succession, and yet studies show that speakers are highly sensitive to these cues and use them to guide interpretation in a rapid and highly incremental fashion. The chapter examines studies from the psycholinguistic literature with a focus on three aspects of event structure: manner and result verbal meanings, temporal boundaries of events, and the encoding of event participants.